Involvement of immature endothelial cells in vascular alterations in Alzheimer’s disease - Frontczak-Baniewicz, Małgorzata; Andrychowski, Jarosław; Czernicki, Zbigniew; Walski, Michał (Folia Neuropathologica, 2006)
The aim of the present study was to investigate ultrastructural features of cerebral capillaries and the pattern of new vessel formation in a patient with Alzheimer’s disease (AD). Recent neuropathological studies have demonstrated that patients with AD have cerebrovascular pathology. Using electron microscopy, we showed that alterations of the capillaries are a common finding both in vascular disease and in AD, suggesting that vascular factors may also play a role in the pathogenesis of AD. We also found regionally increased capillary density, and in many sections immature endothelial cells lying on the preexisting endothelium were present in the lumen of capillaries. These cells might thus contribute to the pathological pattern of capillaries. The cytoplasm of immature endothelial cells in the patient with AD was characterized by accumulation of amyloid fibrils. We suggest that immature endothelial cells may be an important source of circulation-derived amyloid in the brain.